Axiological dominants of paremies as typological markers in Russian, Tuvan and French ethnic cultures - Neliubova , Natalia Yu. (The New Research of Tuva, 2022)
Making use of paremiological units in Tuvan linguistic culture, the article aims to examine the general hierarchy of axiological dominants of an ethnic culture. The outcomes of this examination are then compared with those previously obtained by the author through the analysis of Russian and French paremies. For its source materials, the study relies on published collections of Tuvan proverbs and sayings, as well as on the most authoritative paremiological dictionaries of Russian and French languages.In the methodological sense, the study is based upon the idea that the names and contents of thematic classes that objects within paremiological sources fall into correctly reflects the major qualitative and quantitative characteristics of the conceptual sphere and the subsystem of moral values within the ethnonational world picture that it corresponds to.The article proves that for all of the three ethnic cultures, there are common axiological dominants of typological importance, such as ‘family’, ‘work’, ‘friendship’ or ‘faith’. Being universal in character, they, however, occupy different places in the hierarchy of moral values within each ethnic culture. ‘Man’ as an axiological domimant, for instance, is barely present in Tuvan culture, and only occasionally appears in Russian, while in French it has a dominant presence within thematic classes of paremies. This leads to a conclusion that ethnic cultures may have an individualist (e.g., French) or a collectivist (e.g., Tuvan or Russian) character. Another set feature of Tuvan ethnic culture is the dominant binomiality ot ‘people’ and ‘Motherland’, thus  revealing the highest importance these values occupy within the traditional worldview of Tuvans.
Keywords: ethnic culture; axiology; hierarchy of values; axiological dominant; paremiology; Tuvan language; Tuvan culture; Tuvan folklore; Russian language; French language